12th IFIP/IEEE International Symposium on Integrated Network Management (IM 2011) and Workshops 2011
DOI: 10.1109/inm.2011.5990564
|View full text |Cite
|
Sign up to set email alerts
|

Effective VM sizing in virtualized data centers

Abstract: Abstract-In this paper, we undertake the problem of server consolidation in virtualized data centers from the perspective of approximation algorithms. We formulate server consolidation as a stochastic bin packing problem, where the server capacity and an allowed server overflow probability p are given, and the objective is to assign VMs to as few physical servers as possible, and the probability that the aggregated load of a physical server exceeds the server capacity is at most p.We propose a new VM sizing ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(63 citation statements)
references
References 8 publications
0
63
0
Order By: Relevance
“…Innovative DCIM support systems for datacenter management are thus needed. PMSM (i.e., Power Monitor System and Management) [44][45][46][47][48][49][50][51][52][53][54][55][56], developed at EPFL in cooperation with Credit Suisse [45], is an example of such an innovation.…”
Section: Monitoring System For Datacentersmentioning
confidence: 99%
See 2 more Smart Citations
“…Innovative DCIM support systems for datacenter management are thus needed. PMSM (i.e., Power Monitor System and Management) [44][45][46][47][48][49][50][51][52][53][54][55][56], developed at EPFL in cooperation with Credit Suisse [45], is an example of such an innovation.…”
Section: Monitoring System For Datacentersmentioning
confidence: 99%
“…In [51], Verma et al found out that workloads running on datacenters are strongly correlated one another. In order to achieve further power savings while maintaining quality of service (QoS) level, correlations among VMs' workload have been exploited in recent works [51][52][53][54]. In [51], Verma et al presented a clustering-based correlation-aware VM placement solution.…”
Section: Correlation-aware Power and Temperature Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…There are existing tools for monitoring and collecting hardware configuration information, and VM resources usage traces, such as IBM Tivoli Monitoring (ITM) [1], which is currently used by our industrial partner. VMs' resource demands can also be forecasted by several techniques such as the ones presented in [9,12]. Filling the DB is, however, out of the scope of this paper.…”
Section: Soc System Architecturementioning
confidence: 99%
“…In on-demand clouds, there are potentially two types of VM-placement decisions to be made: (1) initial placement [13][14][15][16][17][18][19][20][21][22][23] and (2) migration (and/or resizing) of VMs over time [24][25][26][27][28][29][30], as PM availability changes, as consolidation is needed to conserve power and in response to the degree to which service-level agreements (SLAs) are being achieved. Most previous research on initial VM placement considered only PMs within a single cloud, but in one case [22] placement decisions considered which of several clouds to choose.…”
Section: Related Workmentioning
confidence: 99%